The role of parental expectations in understanding social and academic well-being among children with disabilities in Ireland. Issue 4 (1st October 2016) - McCoy, Selina; Maître, Bertrand; Watson, Dorothy; Banks, Joanne
Abstract: This paper draws on longitudinal data to examine the extent to which parents' educational expectations shape academic development and changes in self-concept among young people with different types of disability. The analysis is based on the Growing Up in Ireland longitudinal study, which tracked 7423 children between the primary to secondary school years, 21% of whom were identified with one of four main disability types. Our conceptual framework assumes that parental expectations at age 9 will be influenced by both the child's disability and child's academic achievement at that stage, as well as being influenced by other factors such as parent's own education, family economic vulnerability, family relationships and family structure. Therefore, we take these factors into account in tracing the consequences of parental expectations at age 9, on academic and social outcomes at age 13 after the transition to secondary education. Among young people with a disability, poorer self-concept at age 13 is partly explained by lower parental expectations, particularly for those with general learning and emotional/behavioural disabilities. Similarly, parental expectations are a significant influence on children's academic outcomes and partly explain the effects of disability status on academic development. Parents' beliefs about their children's abilities have a strong influence on achievement and self-concept, raising important issues around the need to promote equality of opportunity, raising awareness of the educational opportunities available, promoting positive expectations and engagement with school and the importance of promoting a range of opportunities for achievement.